Space Diversity Mitigation Effects on Ionospheric Amplitude Scintillation with Basis on the Analysis of GNSS Experimental Data - Costa, Emanoel; Moraes, Alison de O.; De Paula, Eurico R.; Monico, Joao Francisco G. (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Ionospheric density irregularities embedded in Equatorial Plasma Bubbles, with scale sizes varying from several hundred kilometers to several tens of meters, may cause amplitude and phase scintillation of transionospheric radio waves, degrading the performance and availability of space-based communication and navigation systems. A recent computer simulation study, based on ionospheric irregularities detected by the Planar Langmuir Probe onboard the Communication/ Navigation Outage Forecasting System satellite, analyzed the mitigation effects from space diversity on amplitude scintillation of transionospheric signals received on the ground. The present work, based on experimental data, will confirm and extend the previous results, indicating, in statistically quantitative terms, how space diversity, effective on uplink and downlink ground-satellite paths, particularly in the strong and saturated scintillation regimes, depends on Ionospheric Pierce Point dip-latitude and distance intervals, as well as on a well-known amplitude scintillation index.
Keywords: Amplitude scintillation index; Downlink; Equatorial Plasma Bubbles (EPBs); Global navigation satellite system; Global Navigation Satellite Systems (GNSS); Indexes; ionospheric density irregularities; Monitoring; Satellites; space diversity; Space vehicles; Spatial diversity